TECHNOLOGY-ENHANCED LANGUAGE LEARNING: Choices, attitudes and recommendations from previous research - Dauzón-Ledesma, Leonor; Izquierdo-Sandoval, Jesús Manuel (Cinzontle, 2018)
The fast development of technology itself and applications that can be used for language learning has prompted the use of new instructional aids for language teaching. On the one hand, it is important to consider that the everyday use of technology could enhance language instruction and learning attitudes (Izquierdo, Simard & Garza, 2016); through its use, learners can retain content in the new language and internalize linguistic resources available in the content they cover. On the other hand, the use of some types of technologies, such as the internet and social networking bring out some issues, as they could represent a risk, possi-bilities of misinformation, inappropriate language use or access to offensive material (OECD, 2015). Consequently, careful planning and selection of the technology resources are of great importance for language teachers.